Governance in Santiago de Chile - stakeholder prospects for the future - Cornelia Hölzl; Henning Nuissl (Helmholtz-Zentrum für Umweltforschung (UFZ), 2010)
With the objective of promoting sustainable development in Santiago de Chile, this paper explores current challenges and possible future trends of urban governance from a local stakeholder point of view. Its empirical base is an online survey conducted among local stakeholders in spring 2009. It brings together the opinions of nearly fifty stakeholders from different sectors, e.g., political decisionmakers, experts from the private sector, NGOs and universities. Data was also gathered in a focus - group discussion realized carried out with selected participants of from the survey. This data enables us to make assumptions about the urban development challenges Santiago is confronted with as well as upcoming governance processes. It furthermore allows us to critically reflect stakeholder perceptions of metropolitan development trends. Urban governance in Santiago is first of all characterized by the fact that Chile is still a highly centralized country. Accordingly, the stakeholders who took part in our study are particularly concerned with the issue of decentralization and most of them call for a more determined delegation of competencies and tasks away from the national level to regional and local authorities. The development of citizen participation, another vital aspect, appears to be slow in Santiago and will need more encouragement and support if it is to flourish. With respect to more tangible, i.e., material, urban development challenges, the stakeholders we interviewed see the greatest demand for action in the fields of air protection, public transport and the provision of green areas.
Keywords: 300